Establishment of the regional centre for techical servise and monitoring of exploitation of agricultural machinery - Legeza, Daria; Легеза, Дар'я Георгіївна; Легеза, Дарья Георгиевна; Kulish, Tatiana; Куліш, Тетяна Володимирівна; Кулиш, Татьяна Владимировна (ТДАТУ, 2013)
The expediency of establishing the regional center of technical service and monitoring of exploitation agricultural machinery is grounded. Objectives, economic features of the project and monitoring are set. Methodology of monitoring of exploitation in the center is proposed.
Keywords: agricultural machinery; technical service; maintenance